Edukasi dan Pengenalan Cabang Olahraga Menembak untuk Anak Sekolah Dasar dan Menengah Pertama sebagai Upaya Peningkatan Prestasi Olahraga Menembak Tingkat Pelajar Kota Semarang: Edukasi dan Pengenalan Cabang Olahraga Menembak untuk Anak Sekolah Dasar dan Menengah Pertama sebagai Upaya Peningkatan Prestasi Olahraga Menembak Tingkat Pelajar Kota Semarang - Wahyu Ragil Kurniawan; Mugiyo Hartono; Dwi Gansar Santi Wijayanti; Bhayu Billiandri; Setiawan Jati Utomo; Muhammad Fajar Arif; Rahmi Eka Putri; Muhammad Sony Sugiharto (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2022)
Education and Introduction Shooting Sports for Elementary and Junior High School Children, which was held on October 26, 2021, in partnership with the Central Java Provincial PERBAKIN Supervisor, is a form of community service by lecturers at the Faculty of Sports Science, Universitas Negeri Semarang. Introducing shooting sports, is one of the solutions to be able to generate student interest in learning shooting sports, in the long term it will have an impact on increasing young shooting athletes in Semarang. The material presented contains basic shooting techniques, various numbers in shooting, facilities and infrastructure, as well as an overview of future achievement opportunities for participants who are interested in pursuing shooting sports. Participants’ response showed enthusiasm by asking some questions. Some said that they got new information and knowledge related to shooting. The conclusion of the service carried out received a positive response from the participants. Suggestions of this service are addressed to the Central Java Provincial PERBAKIN Supervisor, especially in the field of Organization to collaborate with the local education office regularly to hold similar activities for education levels from elementary to high school in order to expand opportunities to continue the generation of shooters in the future